Reaksi kimia organik dalam sintesis senyawa bioaktif: Tinjauan mekanisme dan aplikasinya dalam industri farmasi - shochichah, ziya datun (Maliki Interdisciplinary Journal, 2026)
A profound understanding of organic chemical reaction mechanisms is the primary foundation for the development of the modern pharmaceutical industry. This article provides a comprehensive review of the application of various organic reactions in the synthesis of bioactive compounds, ranging from fundamental mechanisms like nucleophilic substitution to cutting-edge techniques such as transition metal catalysis and asymmetric synthesis. The literature review indicates that selecting appropriate synthetic routes, such as utilizing Suzuki-Miyaura and Heck coupling reactions, is critical for determining efficiency and selectivity in producing complex drugs like losartan and naproxen. Furthermore, stereochemical aspects through asymmetric catalysis are proven crucial in ensuring pharmaceutical product safety to avoid toxic side effects resulting from differing activities between enantiomers. The article also emphasizes the importance of integrating green chemistry principles and flow chemistry technology to create production processes that are more efficient, safe, and sustainable. The author concludes that mastering organic reaction mechanisms, combined with technological innovation, is the key to addressing global health challenges and discovering new drugs in the future.